Flower-like Ni0·85Se nanosheets with enhanced performance toward hybrid supercapacitor. (20th October 2019) - Kuai, Yuqing; Wang, Tianlei; Liu, Meitang; Ma, Hongwen; Zhang, Chongji
Abstract: Flower-like Ni0·85 Se nanosheets (Ni0·85 Se-16 h) are synthesized by a two-step hydrothermal method. The electrochemistry performance and phase transformation of nickel selenides which obtained from different reaction times are examined. All the nickel selenides experience the phase transformation process. However, the opened flower-like Ni0·85 Se-16 h sample takes the phase change process more slowly than others. In addition, the electrochemical properties differences between flower-like Ni0·85 Se-16 h and NiO are also studied. Ni0.85 Se-16 h exhibits a areal capacitance of 3.35 F cm −2 at 4 mA cm −2 which is approximately 3.6-fold higher than that of NiO. Then, the hybrid supercapacitor is assembled by using Ni0·85 Se-16 h as a positive electrode and activated carbon as a negative electrode. The hybrid configuration could acquire a high energy density of 44.2 Wh kg −1 at a power density of 888.9 W kg −1, and 28.5 Wh kg −1 at 12825 W kg −1 . The above results emphasize the fact that the opened flower-like construction could effectively promote the electron/ion transportation in the interface between the electrolyte and the active materials which delay the phase transition process and prove the fact that selenization process could enhance the areal capacitance more effectively than oxidation process. Thus, make it a potential candidate as battery-like electrode materials for hybrid supercapacitors.